GENETIC CONTROL OF SOYBEAN RESISTANCE TO SOYBEAN POD SUCKER (Riptortus linearis L.) - Asadi Asadi; Aziz Purwantoro; Sahiral Yakub (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2012)
Riptortus linearis represents the most common pod sucking pest on soybean. Genetic studies on inheritance of resistance to the pest are needed. The study used B4400 and B3802 genotypes as resistant parents, Tambora as susceptible parent. Crosses were made to form F2 population of Tambora x B4400, and Tambora x B3802. A total of 10-20 seeds each of resistant and susceptible parents, 220 F2 seeds of Tambora x B4400 crosses, and 232 F2 seeds of Tambora x B3802 crosses were grown in pots, one plant/pot. The plants were infested with adult R. linearis (riptortus), at the R2 stage. The results showed that the population of riptortus in each of the F2 soybean population at 7 and 15 days after infestation were >2 insects/25 plants, which enables the study of genetic resistance to soybean pod sucker. Heritability values indicated that resistance to pod sucker was controlled by genetic factors. The resistance to riptortus in B4400 and B3802 genotypes was controlled by two recessive genes located at different loci, and interacted with each other with epistatic dominant reaction. With an assumption that B and C genes were dominant, hence the resistance genes found in both soybean genotypes were bbcc. Keywords: genetic resistance, soybean pod sucker Riptortus linearis L.